Beneath the Surface of the First World Ocean Assessment: An Investigation Into the Global Process’ Support for Sustainable Development - Fawkes, Kyle William; Cummins, Valerie (Frontiers in Marine Science, 2019)
The United Nations’ 2030 Sustainable Development Goals have articulated sustainable development requirements at the international level. SDG14: life below water, has in particular, provided a future pathway for sustainable ocean development. With the establishment of this global perspective has come a renewed emphasis on the need for global ocean knowledge production. The 2015 First World Ocean Assessment (FWOA), which was produced by the first cycle of the United Nations’ Regular Process for Global Reporting and Assessment of the State of the Marine Environment, including Socio-economic Aspects, is widely viewed as a primary tool to guiding action on SDG14. This research investigates how effective the FWOA has been at supporting these efforts toward sustainable ocean development. We use a combination of approaches, including document mining, an internationally distributed survey and semi-structured interviews to better understand the impact of the FWOA as well as the interrelated functioning of the Regular Process’ first cycle. While the FWOA was successful in compiling well accepted and credible ocean information, it was unable to generate the impact on sustainable ocean management activities that had originally been expected of it. Funding restrictions, participation issues and political anxieties seemed to derail the first cycle of the Regular Process from initial recommendations and directed the process into unorthodox operations and substantial political control. With the Second World Ocean Assessment (SWOA) well underway, it is imperative that trust is built and social learning is encouraged between participants in the Regular Process.